rs12480307 and rs6050307 Polymorphisms of VSX1 Gene in Patient with Keratoconusin Southwest Iran Using PCR-RFLP - Raziyeh KARAMI ESHKAFTAKI; Effat FARROKHI; Fatemeh HEYBATI GOJANI; Najmeh SALEHI VANANI; Maryam KARAMI ESHKAFTAKI; Ezzatollah MEMARZADEH; Morteza HASHEMZADEH CHALESHTORI (Tehran University of Medical Sciences, 2018)
No Abstract###